2022
DOI: 10.3389/fimmu.2022.847050
|View full text |Cite
|
Sign up to set email alerts
|

What's Race Got to Do With It? CRP Levels in Immune Mediated Skin Diseases: Considerations for Hidradenitis Suppurativa

Abstract: Currently, there is a lack of racial/ethnic heterogeneity in research databases, exposing a systematic issue in studies exploring inflammation-mediated diseases, such as hidradenitis suppurativa (HS). HS is a chronic inflammatory skin condition that disrupts normal structure and functioning of terminal hair follicles, resulting in the formation of recurrent abscesses, nodules, and sinus tracts within intertriginous regions. Studies have described higher serum levels of inflammation-mediated C-reactive protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
(30 reference statements)
1
2
0
Order By: Relevance
“…Expectedly, our findings demonstrated that the clinical efficacy of AG + AE was observably better than that of AG alone. As previously described, the increase in CRP levels helps predict whether patients are resistant to antidepressant therapy 41 . Interestingly, the initial findings of our study revealed that serum levels of CRP in remitters and responders were diminished after treatment with AG or AG + AE, but not significantly in nonresponders, suggesting that serum CRP levels were lower in both remitters and responders than those in nonresponders.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Expectedly, our findings demonstrated that the clinical efficacy of AG + AE was observably better than that of AG alone. As previously described, the increase in CRP levels helps predict whether patients are resistant to antidepressant therapy 41 . Interestingly, the initial findings of our study revealed that serum levels of CRP in remitters and responders were diminished after treatment with AG or AG + AE, but not significantly in nonresponders, suggesting that serum CRP levels were lower in both remitters and responders than those in nonresponders.…”
Section: Discussionsupporting
confidence: 73%
“…As previously described, the increase in CRP levels helps predict whether patients are resistant to antidepressant therapy. 41 Interestingly, the initial findings of our study revealed that serum levels of CRP in remitters and responders were diminished after treatment with AG or AG + AE, but not significantly in nonresponders, suggesting that serum CRP levels were lower in both remitters and responders than those in nonresponders. As a result, it was reasonable to conclude that the efficacy of AG + AE in MSD patients was related to serum CRP levels.…”
Section: Discussionmentioning
confidence: 54%
“…Despite the above, racial and ethnic differences are minimally represented in HS randomized controlled trials. It is imperative that physicians and researchers promote racial/ethnic diversity during patient recruitment [ 38 , 39 , 40 ].…”
Section: Hs and Race/ethnicitymentioning
confidence: 99%